1988
DOI: 10.1021/bi00425a024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental charge measurement at leaving oxygen in the bovine ribonuclease. A catalyzed cyclization of uridine 3'-phosphate aryl esters

Abstract: The title esters are demonstrated to be specific substrates of bovine pancreatic ribonuclease A (EC 3.1.27.5). The Brønsted dependence of kcat/Km at pH 7.50 for the enzyme-catalyzed cyclization versus the pKa of the leaving phenol exhibits two regression lines of almost identical slope for respectively 2-chlorophenols and 2,6-unsubstituted phenols: log kcat/Km = -0.20 pKa ArOH + 5.47 (n = 5, r = 0.957); log kcat/Km = -0.17 pKa ArOH + 5.79 (n = 4, r = 0.965). Comparison of the Brønsted beta 1g's with that for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 25 publications
(25 reference statements)
3
39
1
Order By: Relevance
“…Consistent with this idea, a ␤ lg of Ϫ0.54 to Ϫ0.59 was determined for an aryl phosphate diester that bears a good leaving group (32). It has been shown that the ␤ lg for a series of aryl-phosphate diester compounds is even less negative (␤ lg ϭ Ϫ0.2) in the active site of RNase A, suggesting a considerable contribution of electrophilic catalysis in the active site (33). Brønsted analysis using aryl-phosphate diester compounds gave a Brønsted coefficient, ␤, of 0.67 (␣ of 0.33) (32,34).…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with this idea, a ␤ lg of Ϫ0.54 to Ϫ0.59 was determined for an aryl phosphate diester that bears a good leaving group (32). It has been shown that the ␤ lg for a series of aryl-phosphate diester compounds is even less negative (␤ lg ϭ Ϫ0.2) in the active site of RNase A, suggesting a considerable contribution of electrophilic catalysis in the active site (33). Brønsted analysis using aryl-phosphate diester compounds gave a Brønsted coefficient, ␤, of 0.67 (␣ of 0.33) (32,34).…”
Section: Discussionmentioning
confidence: 80%
“…This compound was reacted with remote labeled p-nitrophenyl phosphorodichloridate and purified as described above for the natural abundance compound. The compound was SCHEME 2 stored as the 2Ј,5Ј-bis(4-methoxytetrahydropyran-4-yl) ether and deblocked in dilute HCl solution just before use in measurements of bridge- 18 O isotope effects. The achiral 4-methoxytetrahydropyran-4-yl ether protecting group was used to avoid differential rates in the acid-catalyzed removal of the protecting groups which could occur with the chiral tetrahydropyranyl ether.…”
Section: Preparation Of Remote Labeled 2ј5ј-bis(4-methoxytetrahydropmentioning
confidence: 99%
“…NMR experiments monitoring the removal of the tetrahydropyranyl groups versus hydrolysis showed that under these conditions deprotection was complete while hydrolysis of the deprotected diester was undetectable by 13 P NMR. For 15 N isotope effects, the natural abundance 2Ј,5Ј-bis(tetrahydropyranyl)uridine-3Ј-p-nitrophenyl phosphate (1a) was used, and for the 18 O isotope effect experiments, remote labeled 2Ј,5Ј-bis(4-methoxytetrahydropyran-4-yl) uridine-3Ј-p-nitrophenyl phosphate (1b) was used. It was noted that the four diastereomers of 1a resulting from the chiral tetrahydropyranyl groups exhibited slightly different rates of deprotection.…”
Section: General Procedures For Isotope Effect Determinationsmentioning
confidence: 99%
See 2 more Smart Citations